ChemInform Abstract: Pb2PdO2(OH)2 and Pb2PdO(OH)4(H2O): Synthesis and Crystal Growth at Ambient Conditions. Issue 39 (September 2015) - Komarek, Alexander Christoph; Merz, Patrick; Guo, Hanjie; Suard, Emmanuelle; Chen, Jin‐Ming; Felser, Claudia; Jansen, Martin
Abstract The crystal structures of the new compounds (III) and (IV) are determined by powder neutron diffraction and single crystal XRD.